A novel experimental approach for nanostructure analysis: simultaneous small-angle X-ray and neutron scattering - Metwalli, Ezzeldin; Götz, Klaus; Lages, Sebastian; Bär, Christian; Zech, Tobias; Noll, Dennis; Schuldes, Isabel; Schindler, Torben; Prihoda, Annemarie; Lang, Herbert; Grasser, Jürgen; Jacques, Mark; et al. (Journal of Applied Crystallography, 2020)
Exploiting small-angle X-ray and neutron scattering (SAXS/SANS) on the same sample volume at the same time provides complementary nanoscale structural information in two different contrast situations. Unlike an independent experimental approach, the truly combined SAXS/SANS experimental approach ensures the exactness of the probed samples, particularly for in situ studies. Here, an advanced portable SAXS system that is dimensionally suitable for installation in the D22 zone of ILL is introduced. The SAXS apparatus is based on a Rigaku switchable copper/molybdenum microfocus rotating-anode X-ray generator and a DECTRIS detector with a changeable sample-to-detector distance of up to 1.6 m in a vacuum chamber. A case study is presented to demonstrate the uniqueness of the newly established method. Temporal structural rearrangements of both the organic stabilizing agent and organically capped gold colloidal particles during gold nanoparticle growth are simultaneously probed, enabling the immediate acquisition of correlated structural information. The new nano-analytical method will open the way for real-time investigations of a wide range of innovative nanomaterials and will enable comprehensive in situ studies on biological systems. The potential development of a fully automated SAXS/SANS system with a common control environment and additional sample environments, permitting a continual and efficient operation of the system by ILL users, is also introduced.
CRIS-Team WoS Importer:2020-06-19

Area-Selective Growth of HfS(2)Thin Films via Atomic Layer Deposition at Low Temperature - Cao, Yuanyuan; Wähler, Tobias; Park, Hyoungwon; Will, Johannes; Prihoda, Annemarie; Moses Badlyan, Narine; Fromm, Lukas; Yokosawa, Tadahiro; Wang, Bingzhe; Guldi, Dirk Michael; Görling, Andreas; Maultzsch, Janina; et al. (Advanced Materials Interfaces, 2020)
The transition-metal dichalcogenide HfS(2)is a promising alternative semiconductor with adequate band gap and high carrier mobility. However, a controllable growth of continuous HfS(2)films with selectivity for specific surfaces at a low temperature on a large scale has not been demonstrated yet. Herein, HfS(2)films are grown at 100 degrees C by atomic layer deposition (ALD) based on the precursors tetrakis(dimethylamido)hafnium and H2S. In situ vibrational spectroscopy allows for the definition of the temperature range over which (Me2N)(4)Hf chemisorbs as one monolayer. In that range, sequential exposures of the solid surface with (Me2N)(4)Hf and H2S result in self-limiting reactions that yield alternating surface termination with dimethylamide and thiol. Repeating the cycle grows smooth, continuous, stoichiometric films of thicknesses adjustable from angstroms to >100 nm, as demonstrated by spectroscopic ellipsometry, XRR, AFM, UV-vis and Raman spectroscopy, XPS, and TEM. The well-defined surface chemistry enables one to deposit HfS(2)selectively using, for example, patterns generated in molecular self-assembled monolayers. This novel ALD reaction combines several attractive features necessary for integrating HfS(2)into devices.
Keywords: 2D materials; atomic layer deposition; dichalcogenides; hafnium disulfide; thin films

Area-Selective Growth of HfS(2)Thin Films via Atomic Layer Deposition at Low Temperature - Cao, Yuanyuan; Wähler, Tobias; Park, Hyoungwon; Will, Johannes; Prihoda, Annemarie; Moses Badlyan, Narine; Fromm, Lukas; Yokosawa, Tadahiro; Wang, Bingzhe; Guldi, Dirk Michael; Görling, Andreas; Maultzsch, Janina; et al. (Advanced Materials Interfaces, 2020)
The transition-metal dichalcogenide HfS(2)is a promising alternative semiconductor with adequate band gap and high carrier mobility. However, a controllable growth of continuous HfS(2)films with selectivity for specific surfaces at a low temperature on a large scale has not been demonstrated yet. Herein, HfS(2)films are grown at 100 degrees C by atomic layer deposition (ALD) based on the precursors tetrakis(dimethylamido)hafnium and H2S. In situ vibrational spectroscopy allows for the definition of the temperature range over which (Me2N)(4)Hf chemisorbs as one monolayer. In that range, sequential exposures of the solid surface with (Me2N)(4)Hf and H2S result in self-limiting reactions that yield alternating surface termination with dimethylamide and thiol. Repeating the cycle grows smooth, continuous, stoichiometric films of thicknesses adjustable from angstroms to >100 nm, as demonstrated by spectroscopic ellipsometry, XRR, AFM, UV-vis and Raman spectroscopy, XPS, and TEM. The well-defined surface chemistry enables one to deposit HfS(2)selectively using, for example, patterns generated in molecular self-assembled monolayers. This novel ALD reaction combines several attractive features necessary for integrating HfS(2)into devices.
CRIS-Team Scopus Importer:2020-10-23
Keywords: 2D materials; atomic layer deposition; dichalcogenides; hafnium disulfide; thin films

Crystal-structure of active layers of small molecule organic photovoltaics before and after solvent vapor annealing - Berlinghof, Marvin; Langner, Stefan; Harreiß, Christina; Schmidt, Ella; Siris, Rita; Bertram, Florian; Shen, Chen; Will, Johannes; Schindler, Torben; Prihoda, Annemarie; Rechberger, Stefanie; Duesberg, Georg; et al. (Zeitschrift fur Kristallographie - Crystalline Materials, 2020)
It is demonstrated by a detailed structural analysis that the crystallinity and the efficiency of small molecule based organic photovoltaics can be tuned by solvent vapor annealing (SVA). Blends made of the small molecule donor 2,2′-[(3,3′″,3″″,4′-tetraoctyl[2,2′:5′,2″:5″,2′″:5′″,2″″-quinquethiophene]-5,5″″-diyl)bis[(Z)-methylidyne(3-ethyl-4-oxo-5,2-thiazolidinediylidene)]]bis-propanedinitrile (DRCN5T) and the acceptor [6,6]-phenyl C71 butyric acid methyl ester (PC 71 BM) were annealed using solvent vapors with either a high solubility for the donor (tetrahydrofuran), the acceptor (carbon disulfide) or both (chloroform). The samples were analyzed by grazing-incidence wide-angle X-ray scattering (GIWAXS), electron diffraction, X-ray pole figures, and time-of-flight secondary ion mass spectrometry (ToF-SIMS). A phase separation of DRCN5T and PC 71 BM is induced by SVA leading to a crystallization of DRCN5T and the formation of a DRCN5T enriched layer. The DRCN5T crystallites possess the two dimensional oblique crystal system with the lattice parameters a = 19.2 Å, c = 27.1 Å, and β = 111.1° for the chloroform case. No major differences in the crystal structure for the other solvent vapors were observed. However, the solvent choice strongly influences the size of the DRCN5T enriched layer. Missing periodicity in the [010]-direction leads to the extinction of all Bragg reflections with k ≠ 0. The annealed samples are randomly orientated with respect to the normal of the substrate (fiber texture

Epitaxial Metal Halide Perovskites by Inkjet-Printing on Various Substrates - Sytnyk, Mykhailo; Yousefi-Amin, Amir Abbas; Freund, Tim; Prihoda, Annemarie; Götz, Klaus; Unruh, Tobias; Harreiß, Christina; Will, Johannes; Spiecker, Erdmann; Levchuk, Jevgen; Osvet, Andres; Brabec, Christoph; et al. (Advanced Functional Materials, 2020)
Metal-halide-perovskites revolutionized the field of thin-film semiconductor technology, due to their favorable optoelectronic properties and facile solution processing. Further improvements of perovskite thin-film devices require structural coherence on the atomic scale. Such perfection is achieved by epitaxial growth, a method that is based on the use of high-end deposition chambers. Here epitaxial growth is enabled via a approximate to 1000 times cheaper device, a single nozzle inkjet printer. By printing, single-crystal micro- and nanostructure arrays and crystalline coherent thin films are obtained on selected substrates. The hetero-epitaxial structures of methylammonium PbBr(3)grown on lattice matching substrates exhibit similar luminescence as bulk single crystals, but the crystals phase transitions are shifted to lower temperatures, indicating a structural stabilization due to interfacial lattice anchoring by the substrates. Thus, the inkjet-printing of metal-halide perovskites provides improved material characteristics in a highly economical way, as a future cheap competitor to the high-end semiconductor growth technologies.
CRIS-Team Scopus Importer:2020-09-11
Keywords: epitaxial growth; inkjet printing; metal-halide-perovskites; single-crystal-microstructures

Interface between Water-Solvent Mixtures and a Hydrophobic Surface - Prihoda, Annemarie; Will, Johannes; Duchstein, Patrick; Becit, Bahanur; Lossin, Felix; Schindler, Torben; Berlinghof, Marvin; Steinrück, Hans Georg; Bertram, Florian; Zahn, Dirk; Unruh, Tobias (Langmuir, 2020)
The mechanism behind the stability of organic nanoparticles prepared by liquid antisolvent (LAS) precipitation without a specific stabilizing agent is poorly understood. In this work, we propose that the organic solvent used in the LAS process rapidly forms a molecular stabilizing layer at the interface of the nanoparticles with the aqueous dispersion medium. To confirm this hypothesis, n-octadecyltrichlorosilane (OTS)-functionalized silicon wafers in contact with water-solvent mixtures were used as a flat model system mimicking the solid-liquid interface of the organic nanoparticles. We studied the equilibrium structure of the interface by X-ray reflectometry (XRR) for water-solvent mixtures (methanol, ethanol, 1-propanol, 2-propanol, acetone, and tetrahydrofuran). The formation of an organic solvent-rich layer at the solid-liquid interface was observed. The layer thickness increases with the organic solvent concentration and correlates with the polar and hydrogen bond fraction of Hansen solubility parameters. We developed a self-consistent adsorption model via complementing adsorption isotherms obtained from XRR data with molecular dynamics simulations.
CRIS-Team Scopus Importer:2020-10-30

Nucleation Behavior of SnS2 on Thiol Functionalized SAMs During Solution-Based Atomic Layer Deposition - Götz, Klaus; Prihoda, Annemarie; Shen, Chen; Dierner, Martin; Dallmann, Johannes; Prusch, Saskia; Zahn, Dirk; Spiecker, Erdmann; Unruh, Tobias (Advanced Materials Interfaces, 2024)
Solution-based atomic layer deposition (sALD) is an emerging technique that transfers the principle of traditional atomic layer deposition (ALD) from the gas phase into a wet chemical environment. This new preparation technique has new and unique properties and requirements. A large number of new surfaces and reactants are available to produce active 2D materials. In this work a reproducible procedure to coat silicon wafers with a densely packed monolayer of (3-Mercaptopropyl)trimethoxysilane (MPTMS) molecules is presented. These highly functionalized surfaces can be used to seed the nucleation of SnS2 in a solution-based ALD procedure. A coating routine for the production of SnS2 is adapted from ALD to sALD and insight into the nucleation behavior of the reactands is given. X-ray reflectometry (XRR) is used to resolve the nucleation process of SnS2 on an MPTMS self assembled monolayer (SAM) during the first three cycles of an sALD procedure. The comparison of ex situ XRR, in situ XRR, grazing incidence wide-angle X-ray scattering (GIWAXS), atomic force microscopy (AFM), energy dispersive X-ray spectroscopy (EDX) measurements, and density functional theory (DFT) calculations find that SnS2 first forms a closed layer and then continues to grow in islands on thiol functionalized silane SAMs. Subsequent coating cycles will continue the growth of the islands laterally and in height.
CRIS-Team Scopus Importer:2024-08-09
Keywords: AFM; GIWAXS; sALD; SAM; solution atomic layer deposition; XRR

Porphyrin adsorption and ligand exchange at the (110)-TiO2 / organic liquid interface - Götz, Klaus; Stollberg, Isabella; Prihoda, Annemarie; Bertram, Florian; Metwalli, Ezzeldin; Zech, Tobias; Unruh, Tobias (Surface Science, 2022)
Highly efficient dye-sensitized solar cells (DSSCs) have been prepared on the basis of porphyrin dyes with significant success. Recent studies have demonstrated a correlation between the solar cell efficiency and the configuration of the adsorbed porphyrin molecules at the surface of the semiconducting support material. The preparation of dense self assembled monolayers (SAMs) of upright standing porphyrin molecules on TiO2 surfaces was achieved from toluene solutions only when using a molecular exchange reaction. Here, an exchange study of an oleic acid (OLA) SAM on a <110> TiO2 surface by porphyrin molecules is presented. The exchange reaction has been studied by ex-situ as well as in-situ X-ray reflectometry (XRR) measurements. It was found that an almost complete exchange of OLA with porphyrins can be achieved. With increasing coating times the orientation of the porphyrin molecules relative to the substrate surface changed from flat lying to upright standing.
CRIS-Team Scopus Importer:2022-04-15
Keywords: DESY; functionalization; interface; porphyrin; rutile; X-ray reflectometry

Solution-Growth Liquid-Phase Epitaxy of CsPbBr3 on NaCl by Optimizing the Substrate Dissolution - Elia, Jack; Levchuk, Ievgen; Hou, Yi; Matt, Gebhard; These, Albert; Zhao, Yicheng; Zhang, Jiyun; Forberich, Karen; Osvet, Andres; Götz, Klaus; Prihoda, Annemarie; Wu, Mingjian; et al. (Journal of Physical Chemistry C, 2023)
Since the earliest days of liquid-phase epitaxy (LPE) research, substrate stability has been a prerequisite for investigating nucleation and epitaxial growth. For flux- and melt-growth LPE, soluble substrates have always been viewed as problematic and difficult. However, solution-growth LPE transforms this disadvantage into a benefit by facilitating the creation of graded interfaces. In this study, we investigated the nucleation and growth of solution-grown LPE in the evaporation mode of soluble CsPbBr3 on freshly cleaved NaCl single-crystal substrates. Only two of the four main types of CsPbBr3 crystallization observed are epitaxial. The microscopic observation of composition gradients at the interface of CsPbBr3 grains and substrates reveals a promising opportunity to manipulate the lattice constant at the interface by simply controlling the temperature and concentration.
CRIS-Team Scopus Importer:2023-12-08